CHRONIC OCCLUSION OF THE INTERNAL CAROTID ARTERY WITHOUT IMPAIRMENT OF CEREBRAL CIRCULATION: DOES THE EXCEPTION ALWAYS PROVE THE RULE? (CLINICAL OBSERVATION) - O.V. GAYSYONOK, I.N. TOBOLOV (Паёми Сино)
Reliable data on the incidence of internal carotid artery (ICA) occlusion without the development of cerebrovascular accidents are not currently known Limited observational studies on patients with chronic carotid artery occlusion (CCAO) yield varying results regarding the frequency of identifying CCAO without a history of prior cerebral stroke. In this clinical case report, we present an example of ICA occlusion without the development of acute neurological events over a four-year follow-up period. Detailed examination results are presented, enabling us to assess the feasibility of surgical treatment. We analyze factors that may have a protective effect against the development of acute neurological events in this patient category. Not all patients with ICA occlusion experience an acute cerebrovascular event. An analysis of the protective factors in this group of patients may help optimize stroke prevention strategies in individuals with atherosclerotic carotid artery disease.